Students' Perceptions and Effect of Using Google Voice Assistant to Improve Speaking Skills - Darmawan, Kadek Andre (English Education Department STKIP Agama Hindu Singaraja, 2024)
Artificial Intelligence (AI) is a simulation of human intelligence that is modeled on machines and programmed to think like humans. With this AI, it must be utilized as best as possible in the world of education, of course in English. So, AI be used to teach English to students, especially in terms of English speaking skill. This study was conducted to gauge student response to using Google Voice Assistants (GVA) to improve their speaking skills. This study used explanatory sequential mixed methods. The research utilized post test and interview uses the RASE pedagogic theory. Participants included tenth grade students from SMA N 1 SERIRIT. Findings suggest that this application effectively boosts student self-confidence and improves their speaking skills.